PENGEMBANGAN KERIPIK PISANG DAN SERUNDENG KHAS DESA BALAROA BERBASIS KEARIFAN LOKAL - Mohamad Ronal; Linda Atmasari; Anjela Jenista Tuku; Eka De Patmonsela Liow; Abd Kahar; Kahar Kahar (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
This Community Service Program (PKM) was carried out in Balaroa Village with the aim of developing local processed products in the form of banana chips and serundeng as an effort to improve the community’s economy based on local wisdom. Balaroa Village has abundant potential in banana and coconut production, but its utilization has so far been limited to household consumption and the sale of raw materials, which provides low economic value. Through this program, the community was trained in product processing, modern packaging techniques, and marketing strategies to create hygienic products with distinctive taste and attractive visual presentation. The implementation methods included village potential observation, socialization, hands-on training, and continuous mentoring to ensure that the acquired skills can be applied sustainably. The results showed an increase in the community’s ability to produce value-added products, where the banana chips and serundeng gained positive responses from local consumers and have the potential to become signature souvenirs of Balaroa Village. Thus, this program not only contributed to improving the local economy but also played a role in preserving traditional culinary practices based on local wisdom, making them more relevant and competitive in the modern era.